2018
DOI: 10.1038/s41427-018-0028-3
|View full text |Cite
|
Sign up to set email alerts
|

Metal nanofibrils embedded in long free-standing carbon nanotube fibers with a high critical current density

Abstract: With the growth of nanoelectronics, the importance of thermal management in device packaging and the improvement of high-current-carrying interconnects/wires for avoiding the premature failure of devices have been emphasized. The heat and electrical transport properties of the bulk may not be valid in the characterization of a material at the nanometer level, because the phenomena that occur at the interfaces and grain boundaries become dominant. The failure mechanism of bulk metal interconnects has been under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Grujicic et al (2002) have shown that smaller copper concentration leads to smaller and densely distributed nuclei. A similar observation of the grain size of copper on the inside of CNT macrostructures and on the cladding been reported for electrodeposited CNT-Cu by many authors (Yang et al, 2008;Sundaram et al, 2017aSundaram et al, , 2017bChen et al, 2018a;Rho et al, 2018). In Figure 20, the deposition current used in creating 3.5 cm long CNT-Cu fibers (D =~10 μm) is plotted against the recorded stable electrode potential (V vs. Cu/CuSO4 reference electrode) during deposition and the time (s) it took to fully cover the surface of the fiber with copper.…”
Section: Electrochemical Deposition Process On Pristine Cnt Macrostrusupporting
confidence: 84%
See 1 more Smart Citation
“…Grujicic et al (2002) have shown that smaller copper concentration leads to smaller and densely distributed nuclei. A similar observation of the grain size of copper on the inside of CNT macrostructures and on the cladding been reported for electrodeposited CNT-Cu by many authors (Yang et al, 2008;Sundaram et al, 2017aSundaram et al, , 2017bChen et al, 2018a;Rho et al, 2018). In Figure 20, the deposition current used in creating 3.5 cm long CNT-Cu fibers (D =~10 μm) is plotted against the recorded stable electrode potential (V vs. Cu/CuSO4 reference electrode) during deposition and the time (s) it took to fully cover the surface of the fiber with copper.…”
Section: Electrochemical Deposition Process On Pristine Cnt Macrostrusupporting
confidence: 84%
“…To the author's knowledge, the first to report increased electromigration resistance, i.e., ampacity, were Chai et al (2008b), for nanotubes vertically embedded inside a Cu matrix. Since then, several authors (Subramaniam et al, 2013(Subramaniam et al, , 2014Shuai et al, 2016;Sundaram et al, 2017aSundaram et al, , 2018Kim et al, 2018;Rho et al, 2018;Zou et al, 2018) have reported increased ampacity of their CNT-Cu (or graphene-Cu) composites, compared against a copper reference sample in the same set-up. The improvement has been observed for various types of CNT-Cu configurations with both Cu cladding on CNT material and CNTs embedded inside a Cu matrix, with the property measured both perpendicular and parallel to the nanotube alignment.…”
Section: Electrical and Thermal Properties Of Cnt-cu Compositesmentioning
confidence: 99%
“…With the increasing use of modern electric power systems in the aerospace and transportation industries, and the progressive miniaturization of advanced electronic and communication devices, current‐carrying capability and environmental stability of conductors are becoming critical issues. [ 1–4 ] Therefore, there is high demand for more effective material systems to replace traditional metal wires such as copper (Cu) and aluminum (Al) that have been widely used in the past due to their excellent electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The laser pyrolysis method for 3D graphene allows it to efficiently fabricate a manufactured large area, as shown in Figure a. Using this device, they reported the in vivo neural recording experiments performed on rat models. , The low impedance (2 kΩ to 8 kΩ), high CIC (3.1 mC/cm 2 ), and flexibility made the electrodes appropriate for cortical recording and stimulation, showing a high SNR recording on low-amplitude evoked potentials from the rat’s somatosensory cortex.…”
Section: Materials In Neural Interfacesmentioning
confidence: 99%